Esboço crítico da relação trabalho e educação: da desefetivação existente à possibilidade de efetivação do ser social - Sobreira Júnior, Vicente Juriê (2016)
This research is a bibliographical study on education and work relation in contemporary context, seen in some Marxist perspectives, defending the necessity of marxian originality to reflections posed by this text. The basic assertive of such analysis is to indicate the recovery of the proposed issue reaching out for fundaments presented in Marx’s work as a necessity of a secondary theoretical conception presented in radical criticism to capital logic. For such, by Lukács (2010, 2011, 2013), it is revived an onto-materialistic marxian perspective in which the work presents itself as ontological centrality, founding of social being and their other complexes, such as education. The aim of work is apprehension of concrete field of contradiction and not to ontologize work while metaphysical transcendence point. To achieve so, the study deepens discussion on abstract work as predominant form in capital society. Highlighting the work while founding point of social complexes in which crisis dynamic resides in phenomenal form of this abstract work. The growing of an unstable mass of subjects is indicated in which the totality of working time exploitation expands along lifetime. This issue is presented in first section, showing generally the problem in a few possibilities mentioned by some Marxist writers, such as Frigotto, Kuenzer, Ciavatta, Ramos, among others. They proclaim an educational perspective of work as a fundamental need in a possible construction of an integral, omni-lateral, emancipated subject. Therefore, in second section, we go back to some discreet understandings in Mark’s work, indicating education inserted in necessary process to formative character, secondary, nevertheless, in regards to a revolutionary process of transformation. It is emphasized that it is about a founding processing determined in the way men manufacture their material life. The study ends showing by arguments coming from Marx and some authors (LUKÁCS, 2013) among others that depart from this original point), the problem of reformism as conservation, inserted in a mystified fragmented praxis of anti-capitalist struggles, so, denoting the need of a rescue of radical marxian criticism when hinking of a breaking project to capital logic, originating understanding by root.